Ajuste de modelo computacional na dinâmica de estruturas - Souza, Michael Leone Madureira de (2017)
The main objective of this work is to presente model updating analyses. Experimental modal analyses are performed on a simply supported beam. Measurements come from three accelerometers and the input excitation is provided by an impact hammer. The experimental set-up is submitted to a process of assembling and disassembling the beam supports in order to simulate a scenario closer to the real one in which one may face of a modal data. The Young’s modulus and the coefficients of the proportional damping model are considered as the updating structural variables in optimization procedure. Data variability is taken into account along the model updating process by means of the likelihood function and through Monte Carlo simulation analysis. The great number of experimental data allows the likelihood function investigation. The calibrated model is used for damage identification which is simulated by an addition of small masses on the structure. Inverse method is applied to perform this study based on a finite element analysis model updating.